The response of the fourth stage students to publish course lectures on the lecturers' sites of the College of Basic Education and the College of Science, the University of Babylon as a model: A condition study - Hadi Jassim, Muhammad; Kadhim Hantoush, Ahmed (International Journal of Psychosocial Rehabilitation, 2020)
The study aimed to identify the reality of e-learning in the extent of the fourth stage students’ response to the publication of course lectures on the teaching sites of the College of Basic Education and the College of Science at the University of Babylon. A special questionnaire was prepared for this purpose and distributed to students, and the number of the selected sample was 100 male and female students of their kind, with intentional randomness. The research included two aspects: the theoretical aspect of the concept of e-learning, its objectives, importance, quality standards, e-learning tools, types, advantages and disadvantages, and the practical aspect that included the most important findings of the study through statistical analysis and the process of unpacking data The most important results obtained by the study were as follows: The study proved about the axis of positives, the students' assertion that there are laboratories for e-learning that contain a sufficient number of computers in the college with a high rate of (75.5%), while the weakest percentages were the students' inability to build a favorite for Internet sites on their devices in an organized and indexed manner. Very weak, it reached 5.5%. About the negative axis, the study proved that electronic education lacks the human presence and the relationship between the teacher and the student and between the students themselves, and its focus on the two senses of hearing and sight excludes the rest of the other senses at a rate that ranged between 63.3% and 66.7%. As for the lowest percentages of the negatives of electronic education, it was that disruptive devices hinder the educational process by a slight percentage (22.2%).As for the recommendations, the study found the most prominent work to provide halls for the application of elearning, which includes the provision of a sufficient number of modern, advanced computers compared to the number of students that exist mainly in each stage to benefit everyone, including teachers and students alike, and work to organize specialized courses for both teachers and students to provide them with design skills The work of electronic lessons is supervised by specialists in this field, and work is done to spread scientific and technical awareness about the benefits of e-learning and the adoption of advanced educational and scientific strategies in the field of e-learning and the pursuit of employing e-learning in the field of self-education.